2004
DOI: 10.2139/ssrn.724203
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Under the Threat of Expulsion in a Public Goods Experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 29 publications
(18 reference statements)
14
95
0
2
Order By: Relevance
“…The authors also find that the average earnings of participants are higher with either monetary or nonmonetary punishments compared to the baseline situation where no sanctions are available. 29 Cinyabuguma et al (2006) look at punishment from a different perspective by allowing group members the opportunity to expel free-riders by majority vote. This is a between subjects study with each session consisting of 16 participants all belonging to the same group, in a "partners" protocol.…”
Section: Even Non-monetary Punishments Can Sustain Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also find that the average earnings of participants are higher with either monetary or nonmonetary punishments compared to the baseline situation where no sanctions are available. 29 Cinyabuguma et al (2006) look at punishment from a different perspective by allowing group members the opportunity to expel free-riders by majority vote. This is a between subjects study with each session consisting of 16 participants all belonging to the same group, in a "partners" protocol.…”
Section: Even Non-monetary Punishments Can Sustain Cooperationmentioning
confidence: 99%
“…Participants who make high contributions are more likely to leave a larger group and form a smaller one (or even a "single") while free-riders are more likely to join larger groups in order to reap the economies of scale. Charness and Yang (2007) undertake a more elaborate investigation where participants are not only free to leave their current groups as in Ehrhart and Keser (1999) but they can also vote to expel group members as in Cinyabuguma et al (2006). 33 Ones and Putterman (2007) also study the impact of costly punishments in a situation where groups are sorted according to their levels of cooperation and find that groups consisting of participants with similar cooperative tendencies outperform randomly composed groups.…”
Section: Endogenous Sorting Of Participantsmentioning
confidence: 99%
“…Several other experimental studies have found that high contributions can be sustained in voluntary contribution public goods games when subjects are provided with a mechanism to build their groups and control membership composition Cinyabugma et al 2005; Charness and Yang 2014). Chaudhuri (2011) provides a recent review of the literature on cooperation in sorted groups.…”
Section: Related Literaturementioning
confidence: 99%
“…A common paradigm in the study of human cooperation is the multi-player public good/common-pool resource game, where players can cooperate by investing in a communal resource (Fehr and Gächter 2002;Fehr and Fischbacher 2003;Cinyabugama et al 2005;Milinski et al 2006Milinski et al , 2008. Investments are typically doubled by the experimenter and then divided equally among all players, regardless of who contributed.…”
Section: Cooperation: Theory and Realitymentioning
confidence: 99%
“…For example, players can identify and punish freeriders by imposing financial penalties or excluding them from the public good (Fehr and Gächter 2002;Cinyabugama et al 2005;Janssen et al 2010). Reputation effects can also foster cooperation by allowing players to access more cooperative partners (Roberts 1998;Barclay and Willer 2007;Sylwester and Roberts 2010) or by generating benefits in other contexts, for example by increasing their social status (Milinski et al 2002a, b) or attractiveness to the opposite sex (Tessman 1995;Barclay 2010).…”
Section: Cooperation: Theory and Realitymentioning
confidence: 99%